Analysis of economic and social costs of adverse events associated with blood transfusions in Spain - Borja Ribed-Sánchez; Cristina González-Gaya; Sara Varea-Díaz; Carlos Corbacho-Fabregat; Isabel Bule-Farto; Jaime Pérez de-Oteyza (Elsevier, 2018)
Objective: To calculate, for the first time, the direct and social costs of transfusion-related adverse events in order to include them in the National Healthcare System's budget, calculation and studies. In Spain more than 1,500 patients yearly are diagnosed with such adverse events. Method: Blood transfusion-related adverse events recorded yearly in Spanish haemovigilance reports were studied retrospectively (2010-2015). The adverse events were coded according to the classification of Diagnosis-Related Groups. The direct healthcare costs were obtained from public information sources. The productivity loss (social cost) associated with adverse events was calculated using the human capital and hedonic salary methodologies. Results: In 2015, 1,588 patients had adverse events that resulted in direct health care costs (4,568,914€) and social costs due to hospitalization (200,724€). Three adverse reactions resulted in patient death (at a social cost of 1,364,805€). In total, the cost of blood transfusion-related adverse events was 6,134,443€ in Spain. For the period 2010-2015: the trends show a reduction in the total amount of transfusions (2 vs. 1.91 M€; -4.4%). The number of adverse events increased (822 vs. 1,588; +93%), as well as their related direct healthcare cost (3.22 vs. 4.57M€; +42%) and the social cost of hospitalization (110 vs 200M€; +83%). Mortality costs decreased (2.65 vs. 1.36M€; -48%). Discussion: This is the first time that the costs of post-transfusion adverse events have been calculated in Spain. These new figures and trends should be taken into consideration in any cost-effectiveness study or trial of new surgical techniques or sanitary policies that influence blood transfusion activities. Resumen: Objetivo: Calcular por primera vez los costes económicos y sociales relacionados con las reacciones adversas postransfusionales para actualizar estudios e incluirlos en los presupuestos del Sistema Nacional de Salud. En España, anualmente, más de 1500 pacientes sufren dichas reacciones adversas. Método: Se estudiaron retrospectivamente (periodo 2010-2015) las reacciones adversas a la transfusión recopiladas anualmente en los informes nacionales de hemovigilancia. Dichas reacciones se codificaron mediante clasificación de Grupos Relacionados con el Diagnóstico. Los costes directos sanitarios se obtuvieron de fuentes públicas de información. La pérdida en productividad (coste social) asociada a las reacciones adversas se contabilizó utilizando los métodos del capital humano y salarios hedónicos, respectivamente. Resultados: En el año 2015, en España, 1588 pacientes tuvieron reacciones adversas que derivaron en costes sanitarios (4.568.914 €) y costes sociales debido a hospitalización (200.724 €). Tres reacciones adversas resultaron en muerte del paciente (1.364.805 €). Como suma, el coste total de las reacciones adversas a la transfusión fue de 6.134.443 €. Periodo 2010-2015: la tendencia refleja una reducción en el número total de transfusiones (2 vs. 1,91 M€; -4,4%), un incremento en el número de reacciones adversas (822 vs. 1.588; +93%), en costes sanitarios (3,22 vs. 4,57M€; +42%) y en costes sociales (110 vs. 200M€; +83%), y un descenso en costes de mortalidad (2,65 vs. 1,36M€; -48%). Discusión: Por primera vez se han calculado en España los costes de las reacciones adversas a la transfusión. Los nuevos datos y tendencias deberían ser considerados en estudios de coste-eficiencia sobre técnicas quirúrgicas o políticas sanitarias con repercusión en actividades de transfusión sanguínea. Keywords: Adverse effects, Blood transfusion, Health care costs, Costs and cost analysis, Trends, Palabras clave: Reacciones adversas, Transfusión sanguínea, Costes de la atención en salud, Costes y análisis de costes, Tendencias